Primary ciliary dyskinesia: a case report of double DNAH11 mutant alleles - Pîrlog, Lorin-Manuel; Pătrășcanu, Andrada-Adelaida; Kutasi, Eniko; Iordănescu, Irina; Militaru, Mariela Sanda (Medicine and Pharmacy Reports, 2024)
Primary ciliary dyskinesia (PCD), a rare disorder, is genetically varied. Mutations in proteins involved in the structure, function, or assembly of cilia are known to determine situs inversus, male infertility, and chronic destructive airway disease. PCD is inherited by an autosomal recessive pattern of inheritance in most cases. Nonetheless, patterns of autosomal dominant and X-linked inheritance have been mentioned. A history of recurrent upper and lower respiratory tract infections raised clinical suspicion of primary ciliary dyskinesia in a 10-year-old patient. Genetic tests were performed using next-generation sequencing technology (Illumina NextGen) with the multiplex ligation-dependent probe amplification technique for primary ciliopathies and syndromes subject to differential diagnosis. Genetic testing identified two pathogenic variants, not previously associated with a case report in the literature, c.7727A>G (p.Asp2576Gly) and c.8578G>A (p.Gly2860Ser), within the DNAH11 gene, which is associated with autosomal recessive PCD. The result also reported mutations in other genes involved in autosomal recessive PCD (DNAH8, DNAH9 and ZMYND10), which were classified as variants with uncertain clinical significance. Transmission electron microscopy of respiratory cilia and nasal nitric oxide measurement cannot be used to diagnose PCD in patients with DNAH11 mutations because the structure of cilia is normal, and the levels of NO are not constantly low. High-speed video microscopy analysis can be helpful because DNAH11 mutations cause a distinct phenotype of PCD. Nevertheless, the mutation analysis of various PCD-causing genes remains the easiest to conduct and with good results. Genetic research on PCD has identified a number of significant ciliary genes in recent years, offering fresh perspectives on the molecular processes underlying cilia assembly and function. This facilitates the development of new methods for the diagnosis, prevention, and treatment of PCD. However, because it is a highly complex and heterogeneous disease, the field of gene diagnosis and therapy in PCD is still in its infancy.